Surface preparation and double layer effect for silane application on electrogalvanized steel - Seré, Pablo Ricardo (2023)
Silanes are an alternative to replace pretreatments based on Cr(VI) for electrogalvanized steel (ES). As the interaction between the silane and the metal is important to ensure pretreatment efficiency, surface preparation is a critical step. In this sense, the presence of OH groups on the metal surface is essential. In this paper, the surface preparation of ES and a single/double layer application on the corrosion protection afforded by 3-aminopropyltriethoxy silane was studied. The metal surface was cleaned by polishing, electrochemically (employing anodic or cathodic current) or by chemical oxidation. The electrochemical behavior of the cleaned surfaces was analyzed by cyclic voltammetry and electrochemical impedance spectroscopy (EIS). Afterwards, the hydrolyzed silane was applied in a single or double layer. Coatings were characterized by scanning electron microscopy and energy dispersive X-ray spectroscopy, EIS and by exposure to the humidity chamber. Coatings applied on ES cleaned by electrochemical anodic processes or chemical oxidation provided the best protective performance due to a lower surface of zinc exposed to the high humidity environment. Double layer coatings improved protection due to more homogeneous and higher Si content, sealing defects and increasing the thickness of the one-layer protection, enhancing the barrier protection of the silane.